THE IDENTIFYING STAKEHOLDER ROLES IN DEVELOPING COMMUNICATION SKILLS IN ADDRESSING EMPLOYMENT BARRIERS AMONG MALAYSIAN YOUTHS - Tan Shiu Kuan; Puspalathaa Armum; Agnes Indra Chokkalingam (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2017)
There is a growing consensus among the employers and employees on the need for effective communication in the workplace. The youths in the school-to-work transition, however, encounter barriers, particularly in communication, and perceive stumbling blocks in the path of employment. This is an extended challenge among the youths due to communication apprehension. This paper reviews the existing literature on barriers to effective communication and roles in developing communication skills among young people with communication apprehension. With all things considered, we seek to develop a theoretical framework that encompasses potential factors conducive to the communication competence of Malaysian youths. These factors include personal, family and community factors. The proposed framework is focusing on how the present educational setting, society, government and employers are able to contribute in addressing this matter. Thus, it is expected to provide an intensive solution in addressing the communication barriers faced by the youths through a multi-entity engagement.